2016
DOI: 10.1038/ncomms12651
|View full text |Cite
|
Sign up to set email alerts
|

Fat-associated lymphoid clusters control local IgM secretion during pleural infection and lung inflammation

Abstract: Fat-associated lymphoid clusters (FALC) are inducible structures that support rapid innate-like B-cell immune responses in the serous cavities. Little is known about the physiological cues that activate FALCs in the pleural cavity and more generally the mechanisms controlling B-cell activation in FALCs. Here we show, using separate models of pleural nematode infection with Litomosoides sigmodontis and Altenaria alternata induced acute lung inflammation, that inflammation of the pleural cavity rapidly activates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
100
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 100 publications
(107 citation statements)
references
References 52 publications
6
100
0
1
Order By: Relevance
“…Both myeloid cell precursors (CD31/ER-MP58 + ) and mature macrophages (F4/80 + ) have been detected in omental FALCs, suggesting that these lymphoid clusters form permissive microenvironments where the former cells can proliferate locally to be a source of free macrophages within the peritoneal cavity (32). A similar process is likely to take place in FALCs in the mediastinum and pericardium (33, 34). Importantly, FALCs contain type 2 innate lymphoid cells (ILC2) that can support the proliferation of B1 cells through the expression of IL-5 (19).…”
Section: The Structure Of Falcsmentioning
confidence: 81%
See 2 more Smart Citations
“…Both myeloid cell precursors (CD31/ER-MP58 + ) and mature macrophages (F4/80 + ) have been detected in omental FALCs, suggesting that these lymphoid clusters form permissive microenvironments where the former cells can proliferate locally to be a source of free macrophages within the peritoneal cavity (32). A similar process is likely to take place in FALCs in the mediastinum and pericardium (33, 34). Importantly, FALCs contain type 2 innate lymphoid cells (ILC2) that can support the proliferation of B1 cells through the expression of IL-5 (19).…”
Section: The Structure Of Falcsmentioning
confidence: 81%
“…These cytokines are produced in response to IL-33 and IL-25 and promote goblet cell hyperplasia and helminth expulsion (19, 48). Likewise, a recent report has shown that medFALCs and perFALCs respond to both lung infection with the nematode Litomosoides sigmodontis and lung inflammation via fungal allergen inhalation (33). Under these conditions, medFALC stromal cells produce IL-33, which leads to ILC2 activation and IL-5 secretion.…”
Section: Falc Respond To Inflammation and Immunizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Innate lymphoid cells (ILCs), particularly ILC2 cells, are also found in adipose tissues, including the omentum [15, 24]. Like VAT-associated Tregs, ILC2 cells express ST2 and respond to local IL-33 [15].…”
Section: Cellular Composition Of the Omentum And Msmentioning
confidence: 99%
“…Like VAT-associated Tregs, ILC2 cells express ST2 and respond to local IL-33 [15]. Interestingly, the IL-33-induced expression of IL-5 by ILC2 cells in the FALCs of the pericardium promotes the differentiation of local B1 B cells into IgM-secreting cells [15]. Given that ILC2 cells are also present in the omentum, a similar process likely occurs in this location [47].…”
Section: Cellular Composition Of the Omentum And Msmentioning
confidence: 99%